Climate emergency and vocational education and training. Topic of scientific interest: A systematic review of the literature - M.ª de Fátima Poza Vilches; Susana Ripoll Martín; Mª Teresa Pozo Llorente (Revista Española de Pedagogía)
Climate change, the main challenge of the 21st century, demands urgent educational responses and cultural changes. Vocational education and training (VET) is providing an invaluable opportunity to face the climate emergency and stimulate the socio-ecological transition. Therefore, it is necessary to investigate the extent to which the climate emergency constitutes a consolidated topic of study in educational research focused on VET. Using the PRISMA protocol, we have undertaken a systematic review of literature (2015-2024) indexed in SCOPUS, WOS, ERIC, TESEO and SciELO. Microsoft Excel has been used for the content analysis. Based on the categorization of the information, we have responded to nine research questions on contextual characteristics, the methodological framework and the interpretive evaluation of the studies. The results have revealed growing scientific production, especially in Europe and the global south, with a predominance of theoretical studies over participatory ones. Although the central theme has pointed towards critical frameworks and comprehensive solutions, most studies have adopted reformist approaches that minimize community participation. It has also become evident there is a greater concern for detecting problems rather than for clarifying key concepts, which are essential for effective implementation of sustainability. Furthermore, the preference for green knowledge and skills to the detriment of teacher training and collaboration networks could be hindering the integration of good practices and affecting educational quality. It has been concluded that most studies do not address the climate emergency from a holistic and transformative perspective that questions our cultural identity and promotes a new development paradigm in which ecological wellbeing and social aspects are placed as core issues.